Osteosarcoma‐derived extracellular vesicles induce a tumor‐like phenotype in normal recipient cells. Issue 8 (7th March 2018) - Urciuoli, Enrica; Giorda, Ezio; Scarsella, Marco; Petrini, Stefania; Peruzzi, Barbara
Abstract : Osteosarcoma is the most common primary bone cancer and the most frequent cause of bone cancer‐related deaths in children and adolescents. Osteosarcoma cells are able to establish a crosstalk with resident bone cells leading to the formation of a deleterious vicious cycle. We hypothesized that osteosarcoma cells can release, in the bone microenvironment, transforming Extracellular Vesicles (EVs) involved in regulating bone cell proliferation and differentiation, thereby promoting tumor growth. We assessed EV production by three osteosarcoma cell lines with increasing aggressiveness in order to investigate their roles in the communication between osteosarcoma cells and normal recipient cells. Osteosarcoma‐derived EVs were used to treat the murine fibroblast cell line NIH3T3 and to study the induction of tumor‐like phenotypes. Our results showed that osteosarcoma cell lines are able to produce EVs that fuse to recipient cells, with a very high uptake efficiency. The treatment of recipient NIH3T3 with osteosarcoma‐derived EVs induced substantial biological and functional effects, as an enhanced proliferation and survival capability under starved conditions, high levels of activated survival pathways, an increased migration, adhesion, and 3D sphere formation and the acquired capability to grow in an anchorage‐independent manner. Moreover, in murine NIH3T3 we found human mRNAs of TNF‐α, IL‐6, and TGF‐β, as well as a de novo expression of murine MMP‐9 and TNF‐α following the treatment of human osteosarcoma‐derived EVs. Abstract : Extracellular vesicles are arising as new pivotal factors in the field of cell–cell communication, especially in the vicious cycle that cancer cells establish within the tumor lesion. Here, we demonstrated the role of extracellular vesicles produced by osteosarcoma cancer cells in inducing tumor‐phenotype in normal recipient cells.